Pengembangan Pangsa Pasar Terhadap Pelaku UMKM dalam Industri Kreatif - Melissa Damayanti; Wiwin Priana Primandhana (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Micro, Small, and Medium Enterprises (MSMEs) are a crucial sector in Indonesia's economy. The lack of thorough preparation by MSME actors results in suboptimal performance. This journal aims to investigate and outline effective market share development strategies for MSME actors in the creative industry. The method used is literature review. The research results show that market analysis, branding strategies, and understanding customs procedures are key in the market share development of MSMEs.